Broadband near-perfect optical absorbers fabricated with complete spherical platinum shells with and without induced symmetry broken cracks using a simple colloidal route. Issue 16 (17th April 2023) - Liu, Xiaoyu; Fu, Ming; Guo, Zhengjie; Li, Caixia; Wu, Zheli; He, Dawei; Wang, Yongsheng
Abstract : Broadband perfect absorbers with an average absorptivity of 96.2% in the 200–1500 nm are proposed. Complete spherical Pt shells with induced cracks are fabricated from monolayer microspheres along with heating using conformal oxide and metal coating. Abstract : The development of broadband near-perfect optical absorbers using an efficient lithography-free method is crucial for many applications. The self-assembled monolayer colloidal microsphere arrays combined with heating and complete metal coating provided a simple and efficient method for developing a broadband near-perfect optical absorber. The optimal absorber made of platinum spherical shells with induced cracks has an average absorptivity of 96.2% in the wavelength range of 200–1500 nm. The complete platinum spherical shells provided higher absorptivity than the corresponding upper hemispherical shells and lower hemispherical shells due to the high lossy nature and the induced modes coupled with localized plasmonic resonances. The symmetry-broken cracks in the complete spherical platinum shells were induced by heating of the ALD TiO2 layer and shrinking the polymer. The additional resonant modes created by the broken symmetry, such as the tip modes and nanovoid modes, further increased the absorptivity. The high absorptivity was maintained in a wide oblique angle for all polarizations and the absorptivity even increased at larger oblique angles for TM polarization. The moderate coating thickness of the platinum and the moderate interval between the neighboring spherical shells are both important for optimizing absorptivity. The absorptivity data obtained from the simulation and experiment were highly congruent for a range of geometrical parameters.